2022
DOI: 10.1097/gme.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional interventions on the severity of depressive and anxiety symptoms of women in the menopausal transition and menopause: a systematic review, meta-analysis, and meta-regression

Abstract: Importance: Depression and anxiety may significantly affect women during the menopausal transition. In addition to traditional treatment strategies such as hormone therapy, antidepressants, and psychotherapy, nutritional interventions have been increasingly studied, but there is no consensus about their role in this patient population.Objective: This systematic review and meta-analysis aimed to evaluate the effect of nutritional interventions on the severity of depressive (DS) and anxiety (AS) symptoms in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…The guiding principle must be variety in moderation, cutting out excess fat and too salty foods, drinking at least 25 milliliters (ml) of water per kilogram (kg) of body, and giving preference to spices. Obese or over-weighted women need to change their lifestyle and follow a more moderate diet, while the literature discuss the usefulness of some drugs such as orlistat [95][96][97][98].…”
Section: Managementmentioning
confidence: 99%
“…The guiding principle must be variety in moderation, cutting out excess fat and too salty foods, drinking at least 25 milliliters (ml) of water per kilogram (kg) of body, and giving preference to spices. Obese or over-weighted women need to change their lifestyle and follow a more moderate diet, while the literature discuss the usefulness of some drugs such as orlistat [95][96][97][98].…”
Section: Managementmentioning
confidence: 99%
“…This is true during pregnancy when increased physical activity is associated with decreased risk for gestational diabetes, preeclampsia, and gestational weight gain 1 . For those who have experienced menopause, 2 recent meta‐analyses have highlighted the importance of exercise during menopause to improve or decrease the severity of mental health issues such as depression and anxiety 2 , 3 . The current physical activity recommendations for all adults, including those who are pregnant, is 150 minutes of moderate‐intensity physical activity and 2 days of muscle strengthening a week 4 .…”
Section: How Many Daily Steps Are Needed For Health?mentioning
confidence: 99%
“…However, another study failed to observe any significant alterations in VMS and sleep quality when compared to a placebo [28]. A comprehensive review of 32 studies underscored the vulnerability of menopausal women to depression and anxiety [29]. Exploring the interplay of HF, sleep patterns, and depression in women undergoing menopause induced by a Gonadotropin-releasing hormone (GnRH) agonist medication, a study revealed significant associations between increased sleep interruptions, nocturnal HF, and heightened depression scores [30].…”
Section: Introductionmentioning
confidence: 99%